Did the Late Ordovician African ice sheet reach Europe? - Gutiérrez-Marco, J. C.; Ghienne, Jean-François; Bernárdez, Enrique; Hacar, M. P. (Geology, 2010)
Paleovalleys and their infilling successions are described from outcrops and drill cores of the Cantabrian Range (northern Spain). A Hirnantia fauna and associated diamictites with striated lonestones indicate that the paleovalleys are related to the Hirnantian (latest Ordovician) glacial event. Based on overall geometry, depositional facies, and associated deformation structures, the paleovalleys are interpreted as subglacial tunnel valleys. They were most likely related to the North Gondwana ice sheet. The ice sheet therefore reached the Ibero-Armorican domain that was still attached to the Gondwana landmass at least until the latest Ordovician. Peer reviewed